Strategi Peningkatan Pertumbuhan Usaha Mikro di Kabupaten Boalemo Berbasis Perencanaan Partisipatif - R. Hatu, Ratih Ikawaty; R. Hatu, Dewinta Rizky; Gobel, Rahmat Teguh Santoso (Scimadly Publishing, 2025)
The low growth of new entrepreneurs and the high open unemployment rate in Boalemo Regency have become critical issues that affect regional economic development and poverty levels. These challenges are primarily caused by the lack of training, mentoring, and optimal participatory planning, which hinders the confidence and initiative of prospective micro-entrepreneurs. This study uses secondary data obtained through literature review to analyze open unemployment projections based on age group, gender, and education level, as well as the Gross Regional Domestic Product (GRDP) of Boalemo Regency for 2025-2029. The GRDP projection indicates a positive economic trend across various sectors. However, unemployment is predicted to rise among the 35–44 and 55+ age groups. To address this, strategic recommendations are proposed by referring to the Regional Manpower Plan (RTKD) 2025–2029. The study emphasizes the importance of participatory planning through Musrenbang forums that involve micro-business actors. These forums aim to identify operational support needs, business development strategies, and entrepreneurship opportunities that can be translated into concrete programs funded by the regional budget (APBD), thereby encouraging the growth of micro enterprises and reducing unemployment.